Synthesis, characterization and anticoagulant activity of chitosan derivatives - Mohd. Imran; Meenakshi Sajwan; Bader Alsuwayt; Mohammad Asif (Elsevier, 2020)
Chitosan derivatives are reported as anticoagulants in the literature. This work was undertaken to develop novel chitosan derivatives as anticoagulants. The sulfonated derivatives of chitosan were formed by the reaction of chitosan derivatives with chlorosulfonic acid in N,N-dimethylformamide. The structures of these derivatives were established by FTIR and 1H NMR spectra. The prepared derivatives were evaluated for their in vivo anticoagulant effects by the tail bleeding method in Wistar rats utilizing nicoumalone as a standard drug. The results revealed that the sulfonation of the chitosan increases its anticoagulant activity. The developed compounds exhibited faster onset of action and potency than nicoumalone after one hour of the drug administration. The sulphated N-alkyl derivatives of chitosan were more potent anticoagulants than sulfated quaternary derivatives/sulfated chitosan. It is also suggested to develop analogs of Ethyl chitosan sulfate (4b) and Benzyl chitosan sulfate (4c), which may provide some more fruitful anticoagulants having faster onset of action as well as longer duration of action and possessing a balanced hydrophilic/lipophilic character. Keywords: Synthesis, Chitosan derivatives, Sulfonated chitosan, Anticoagulant activity